The Prevalence of Goitre and The Corresponding Iodine Urine Status in Al Haj Yousif Area -Khartoum Bahri- Sudan, 2006 - Kambal, Ietmad A; Ahamed, Zinab A; Bani, Ibrahem; Yousif, Eisa M; Abd-Elgadir, Sonia; Ramdan, Hannan M; Yousif, Hibt El Rahman EM (Gezira Journal of Health Sciences, 2012)
Introduction: In Sudan iodine deficiency disorders (IDD) . is a major public health problem and the current situation is alarming for all parts of the country where nationwide surveys and pilot studies have been conducted. The rates for goitre prevalence call for immediate intervention. Objectives: The major objective of this study is to assess the iodine deficiency situation in Al Haj Yousif area-Alkhartoum Bahri – Sudan. The study was designed to have a precise epidemiological information of iodine deficiency disorders (IDD). Indicators include goiter prevalence and urinary iodine excretion. Method : A cross sectional community – based field study was conducted during June, July 2007, in five zones of Al Haj Yousif area using a multistage random sampling technique. The sample population was selected by house to house visits. One hundred households (average members per house of 7+2) were selected, covering 300 children (age 6–12 years) as subjects for goitre examination, and a sub-sample of 50 children  (16.7%) were chosen at random for urinary iodine level assessment. Results: The result of goitre examination revealed that the prevalence rate of goitre was (23.3%).It was significantly higher in females (26.7%) than males (20.13%). Overall median urinary iodine (UI) was 5.0 μg/dl. For non-goitrous children it was 6.4 μg/dl  and 2.35 μg/dl for grade 1 and grade 2 goitres respectively. Conclusion : The study findings suggest that significant efforts are needed towards achieving the goal of raising the IDD awareness as well IDD elimination. This includes distribution of iodine capsules as a short term strategy and iodized salt as a long term strategy . الملخص: مقدمة : في السودان مشكلة نقصان اليود مشكلة اجتماعية كبيرة والوضع الحالى محزن في كل اجزاء الوطن ولهذا اقيمت دراسات ومسوحات في هذا الشأن حيث وجد أن الوضع يحتاج لتدخل سريع لتحسين الوضع. الأهداف : تقويم وضع عوز اليود في منطقة الحاج يوسف – الخرطوم بحري السودان. صمم البحث للحصول علي معلومات دقيقة عن تفشي إضرار عوز اليود. اشتملت المؤشرات علي الكشف علي تضخم الغدة الدرقية وتحديد نسبة الإنتشار وفحص البول لليود. الطريقة : أجريت دراسة تقاطعية للمجتمع في شهري يونيو  ويوليو 2007م في خمس مناطق من الحاج يوسف. استخدمت عينة عشوائية متعددة المراحل واختير مجتمع العينة بالزيارات المنزلية  اختيرت100أسرة للعينة (متوسط عدد الأسرة 7 + 2) ومنها اختير عشوائياً 300 طفل في المدى العمري (6 – 12 سنة) ،وعينة أخري شملت 50 طفلا ( 16.7%) من العينة الرئيسية لفحص اليود في البول. النتائج : فحوصات تضخم الغدة الدرقية كشفت عن أن معدل الانتشار هو(23.3%) كان أعلى عند الإناث (%26.71) من الذكور (20.13%). المتوسط الحسابي لنسبة اليود في البول لكل أطفال العينة هو 5 ميكروغرام/دسل، والمتوسط الحسابي لنسبة اليود في البول للأطفال الذين ليس لديهم تضخم في الغدة هو 6.4% ميكروغرام/دسل ، أما متوسط اليود في البول لدرجة تضخم الغدة الدرقية 1 و تضخم الغدة الدرقية 2 فهو 3.8 ميكروغرام/دسل و 2.35 ميكروغرام/دسل علي التوالي. خاتمة و توصيات : النتائج الرئيسية لهذا البحث تؤيد وتدعم أن اضطرابات عوز اليود هي مشكلة صحية عامة في الأطفال من عمر6 – 12 سنة في المنطقة. وانه من المهم والضروري وضع برنامج لتحسين وضع اليود في المنطقة ، وذلك بطرح  إستراتيجية قصيرة المدي كتوزيع كبسولات اليود ، وتوفير الملح المزود باليود كإستراتيجية طويلة الأمد ورفع وعي الجمهور عن المشكلة.